Die letterlike vertolking van metaforiese taal in Josua 10:12-14 - Breytenbach, Andries (HTS teologiese studies, 2002)
The literal understanding of metaphoric language in Joshua 10:12-14In this article the well-known passage in Joshua 10:12-14 is critically investigated within the context of the pericope of Joshua 10. A literary critical investigation shows, inter alia, that the oldest version of the pericope probably was a heroic saga of Joshua’s campaign, with the miraculous intervention of YHWH having been “written into” the narrative at a later stage. During the latter process a poetic fragment, the original of which is lost to us, was interpreted literally, thus creating a miracle account. This miracle account serves the main focus of the pericope: YHWH alone makes possible the impossible for his people.